Analysis Learning Profile of Students with Intellectual Disabilities in Studying the Basic Law of Chemistry Using E-LAPD Based Liveworksheets - Wahyu Aprilia Rahmayanti; Hardiani Novianti; Moniqsa Purbo Syahrani; Rusmini; Dian Novita (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the learning profiles of students with intellectual disabilities, focusing on their learning styles in studying the basic laws of chemistry using e-LAPD based Liveworksheets. The participants were three students with intellectual disabilities from SMAN 10 Surabaya. A mixed-method approach with a concurrent embedded model was employed. Qualitative data were collected through interviews and observations and analyzed using Nvivo 11 software, while quantitative data were obtained from pretest and posttest results and analyzed using bar charts and N-Gain scores to measure improvement in learning outcomes. The quantitative data also supported the qualitative analysis of the relationship between learning style tendencies and learning outcomes. The results show that student DA exhibited a kinesthetic learning style, whereas E and RY demonstrated visual learning styles. Students engagement with e-LAPD activities reflected variations in learning style preferences. Quantitative analysis indicated an increase in learning outcomes, with N-Gain scores categorized as high. Therefore, a learning style that matches students characteristics can enhance learning outcomes. Based on these findings, it can be concluded that e-LAPD based liveworksheets can assist in analyzing learning profiles, particularly learning style tendencies that influence the learning outcomes of students with intellectual disabilities.